Information Delivery System Through Kisan Mobile Advisory Services (Indian Journal of Extension Education, 2011)
The KVK catered to the needs of those who are employed and those who whish to be self employed. The main activities of KVK is to update the technical Knowledge and Skills of the farming communities and to train the Farmers and farmwomen in scientific farming and allied fields like Crop production, Seed production, Horticultural crops, Dairy, Fisheries, Agro forestry and other enterprises.Mobile phone is the important ICT tool for faster dissemination of technology almost 70 percent of the world’s mobile phone subscribers are in developing world. Initially we started programme for sending information through Mobile of different stake holder ie. Farmers/ farm women,Extension personnel & Impute supplier. The massage scheduled on every tuesday & friday ie. two massage per farmers in a week. The content development is the very important aspect in the KMA, we are using different step for preparation and verification of the content. This programme was started during 2008-09 to 2010-11 with 1000 farmers those using mobile for this purpose, out of that 150 farmers selected through random sampling method. The impact shows that the sifting of knowledge of the farmers from Low to Medium and High .The timely information reach in farmers which stand first in the rank among other performance parameters. There is a greater role for KMA to provide technical assistance, appropriate technology input and follow systematic approach of encouraging crop production technology and other enterprises in order to enhance adoption of improved technology. Day by day number of beneficiaries increasing in this programme which show the success of the programme.